Post-Keratoplasty Glaucoma in Secondary Trans-Scleral Fixation of Posterior Chamber Intra-Ocular Lens Implant - Imran Akram Sahaf, Abdul Hye, Abrar Ahmad Bhatti, Zahid Kamal Siddiqui (Pakistan Journal of Ophthalmology, 2011)
Purpose: Purpose of this study was to observe the incidence of postkeratoplasty glaucoma in secondary scleral fixation of IOL in patients of aphakia and pseudophakic bullous keratopathy (Group I). These patients were compared, with clinically matched patients, undergoing penetrating keratoplasty with posterior chamber IOL in the presence of capsular support (Group II). Material and Methods: 25 consecutive patients of bullous keratopathy in aphakic eyes without capsular support or in pseudophakic eyes with AC IOLs were included in this prospective study. Penetrating keratoplasty was performed by suturing 0.25 mm larger donor corneal graft with interrupted 10/0 nylon monofilament sutures, after fixing the IOL to the sclera with 10/0 prolene suture. The statistical analysis was performed using Fisher’s exact test and chi-square test 2x2 table. The finding was considered significant at P value < 0.05. Results: The post-operative visual acuity, in the study population as whole, ranged from < 0.05 to 0.33 Snellen’s fraction (i.e. hand movement to 6/18 Snellen’s VA). A statistically significant improvement was noted (p-value < 0.05 using Fisher’s exact test and chi-square analysis), when post-operative visual acuity was compared with pre-operative visual acuity in each group. However, comparing the study groups, there was no statistically significant difference in the post-operative visual acuity (p-value> 0.05). The incidence of post-operative glaucoma was 32% incidence of glaucoma in group I was 40% (10/25 patients) and in group II was 24% (6/25 patients). The difference between the two groups in the post-operative incidence of glaucoma was statistically significant (p value<0.05). Comparing the difference between pre-operative and post-operative incidence of glaucoma, it was statistically significant within the group I (p value<0.05) as a whole (p value < 0.05). Conclusion: While Trans-scleral fixation of posterior chamber intra-ocular lens has a place in eyes lacking capsular support it does lead to higher frequency of post-keratoplasty glaucoma.